Measles outbreak in Nišava and Toplica Districts from 2017 to 2018 - Rančić, Nataša; Stojanović, Miodrag; Milenković, Nikola; Perović, Miodrag; Janićijević, Ivana; Kostić, Marina; Stojanović, Marko; Jovanović, Marko; Ignjatović, Aleksandra; Anđelković Apostolović, Marija (Acta medicae Medianae, 2021)
AbstractIntroduction. Measles was the leading cause of death among children under 5 years of age before the introduction of obligatory vaccination.The objective of the paper was to describe the epidemiological and clinical characteristics of the affected in the large measles outbreak in 2017-2018 in the Nišava and Toplica Districts.Material and MethodsDescriptive study was done. For the investigation of the outbreak, the general principles of the case definition of the European Union (EU) Commission Decision of 2012 were used. Laboratory investigations of initial patients were conducted at the Center for Control and Prevention of Diseases in the Institute of Public Health Niš, and all specimens were sent and were tested for anti-measles IgM/IgG antibodies in referent laboratory of the Institute of Virology, Vaccines and Sera "Torlak" in BelgradeResults A total of 1327 (584 in  males and 743 in females) cases were reported since 23 November up to 28 July 2018, when it ends. The average age was 35 years ranged from
Keywords: measles; outbreak; vaccination status; vaccination caverage; complications